Potensi Air Kelapa Hijau Dan Kompres Hangat Dalam Mengatasi Dismenore Primer Pada Remaja Putri: Studi Di PMB S Tahun 2023 - Sukemi Susilawati; Ratna Wulandari; Ageng Septa Rini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Based on adolescent report from Pandeglang Regency Health Office, there are 1178 cases of menstrual disorders in adolescents. Based on adolescent program report at UPTD Puskesmas Cikeusik until November 2022, 43.5% of adolescents experience dysmenorrhea or menstrual disorders. The impact of dysmenorrhea causes discomfort, difficulty concentrating in learning and decreased motivation to learn because of the pain felt, can limit women to carry out daily activities so that the need for handling dysmenorrhea in adolescents. The aim is to determine the effectiveness of green coconut water on reducing primary dysmenorrhea pain in adolescent girls in 2023. The sample population in this study were 2 respondents, namely adolescents who experienced primary dysmenorrhea by comparing directly to the response of green coconut water and warm water compresses. The research time was carried out on February 6, 2024 to February 10, 2024 and February 9 to February 11, 2024. Methods Data collection methods by means of assessment, namely interviews to explore the data needed related to the research to be carried out on adolescent girls with primary dysmenorrhea. The results showed a reduction in the pain scale after being given green coconut water. Conclusion In the results of the study, significant results were obtained in reducing primary dysmenorrhea, namely drinking green coconut water 1-3 days of menstruation, because the results obtained reduced pain from scale 4 to scale 2. Suggestions It is expected to apply the green coconut water method and warm water compresses on reducing dysmenorrhea pain.